СТРАТЕГІЧНИЙ АНАЛІЗ ТРАНСФОРМАЦІЙНИХ ЗМІН МІЖГАЛУЗЕВОЇ ВЗАЄМОДІЇ В УМОВАХ ВИКОНАННЯ ОБМЕЖЕНЬ ЗІ СКОРОЧЕННЯ ЕМІСІЙ ПАРНИКОВИХ ГАЗІВ (International Journal of Innovative Technologies in Economy, 2018)
Prospective analysis of contemporary both theoretical and practical economy growing trend demonstrates account social factors and life support on Earth on a global scale. It is expected that in the near future this trend will occupy a major position in the global economy and will significantly determine the international economic relations. At the forefront of a globalizing world economy and international economic relations serves full priority to ensure the future world society. In the article is proposed a modified balance ecological and economic "input-output" model, which is based on established by the Paris Agreement limits on greenhouse gas emissions. It is determinated the conditions for the existence of the productivity model, which provides non-negativity of the economic and environmental performance. It is offered the mathematical apparatus of determining the change in the volume of gross output of primary and secondary production in the event of changes in the sector structure.